Non-Stimulatory pMHC Enhance CD8 T Cell Effector Functions by Recruiting Coreceptor-Bound Lck - Zhao, Xiang; Wu, Liang-Zhe; Ng, Esther K. Y.; Leow, Kerisa W. S.; Wei, Qianru; Gascoigne, Nicholas R. J.; Brzostek, Joanna (Frontiers in Immunology, 2021)
Under physiological conditions, CD8+ T cells need to recognize low numbers of antigenic pMHC class I complexes in the presence of a surplus of non-stimulatory, self pMHC class I on the surface of the APC. Non-stimulatory pMHC have been shown to enhance CD8+ T cell responses to low amounts of antigenic pMHC, in a phenomenon called co-agonism, but the physiological significance and molecular mechanism of this phenomenon are still poorly understood. Our data show that co-agonist pMHC class I complexes recruit CD8-bound Lck to the immune synapse to modulate CD8+ T cell signaling pathways, resulting in enhanced CD8+ T cell effector functions and proliferation, both in vitro and in vivo. Moreover, co-agonism can boost T cell proliferation through an extrinsic mechanism, with co-agonism primed CD8+ T cells enhancing Akt pathway activation and proliferation in neighboring CD8+ T cells primed with low amounts of antigen.